2004
DOI: 10.1525/mp.2004.22.2.265
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptual Structure of Thematic Materials in The Angel of Death

Abstract: The perceptual structure of the five themes of Roger Reynolds's The Angel of Death was investigated. We studied how listeners follow the musical progression of each theme and whether or not they perceive the temporal implications. In the first phase, participants performed three tasks on the full themes, one of which consisted of segmenting the musical ideas online. In the second phase, participants were presented with pairs of excerpts from the themes, judged whether both belonged to the same theme, and if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
5
18
0
Order By: Relevance
“…Evidence on failure of perception of large-scale musical features such as tonal closure support this view (Cook, 1987). Evidence on the short time scale does suggest that listeners perceive segmentation in a manner largely influenced by surface events in the sound stream (Deliège, et al, 1996;Lalitte et al, 2004). The approach taken in the current study allows listeners to identify change for themselves, and deals directly with the sonic temporal patterns that they hear, and which therefore are likely to influence them affectively.…”
Section: Discussionmentioning
confidence: 57%
“…Evidence on failure of perception of large-scale musical features such as tonal closure support this view (Cook, 1987). Evidence on the short time scale does suggest that listeners perceive segmentation in a manner largely influenced by surface events in the sound stream (Deliège, et al, 1996;Lalitte et al, 2004). The approach taken in the current study allows listeners to identify change for themselves, and deals directly with the sonic temporal patterns that they hear, and which therefore are likely to influence them affectively.…”
Section: Discussionmentioning
confidence: 57%
“…This set of data is all the more puzzling in that other studies carried out with atonal musical pieces revealed some ability to perceive the overall organization of a musical atonal piece (Deliège;Clarke & Krumhansl, 1990). Lalitte et al (2004) investigated the perceptual structure of the five themes of The Angel of Death by Roger Reynolds. In the first phase, participants performed segmentation of the musical ideas while listening to the piece.…”
Section: Cognitive Psychology Perspectivementioning
confidence: 99%
“…This latter result demonstrates the role of dynamic memory processes in macrostructural perception in the absence of strong discontinuities in the musical surface. Taken together, these results suggest that this technique is sensitive to structural properties at different levels of abstraction from the sound events, including qualitative and temporal discontinuities, structural markers such as repetition and return, and rhetorical functions such as continuity, development, and digression (see Lalitte et al, 2004). Weak discontinuity NOTE-I = Instrumentation, MT = musical texture, TD = temporal density, D = dynamics, P = existence of a pause or silence.…”
Section: Discussionmentioning
confidence: 93%
“…Each theme is composed of several subsections, one of which is considered to be central to the temporal trajectory of the theme: the core element (gray rectangles in Fig. 1; see Lalitte et al, 2004). In addition to the themes, there are other developmental sections in which transitions between thematic materials occur (TR13, TR24) or in which thematic materials are combined in parallel (CB24, CB35, CB123).…”
Section: The Piece the Angel Of Deathmentioning
confidence: 99%